Molecular studies of coralberry (Ardisia crenata Sims; Primulaceae) from Thailand based on SCoT markers - SUPARMAN SUPARMAN; PIMWADEE PORNPONGRUNGRUENG; PRANOM CHANTARANOTHAI (Society for Indonesian Biodiversity, 2023)
Abstract. Suparman S, Pornpongrungrueng P, Chantaranothai P. 2023. Molecular studies of coralberry (Ardisia crenata Sims; Primulaceae) from Thailand based on SCoT markers. Biodiversitas 24: 3183-3189. A coralberry (Ardisia crenataSims) is the most common species of Ardisia Sw. distributed widely in Thailand. The grouping of the species for intraspecific based on morphometric characters was unstable. Some molecular primers were used by researchers to separate species. In this molecular study, six selected SCoT of 36 primers, i.e., primers no. 13, 14, 15, 19, 20, and 21, displayed high polymorphic and resolving power in A. crenata from 14 different natural populations in Thailand. This marker separated all taxa into two groups from different floristic regions. In contrast, this result did not support the classification of the intraspecific level of A. crenata based on continued morphological characteristics. For the conclusion that this study was recorded as the first one using the SCoT marker on the Ardisiaand the primer worked well in A. crenata and was recommended for other species in Ardisia.